Ligand Bias and Its Association With Pro-resolving Actions of Melanocortin Drugs - Patruno, Sara; Garrido-Mesa, Jose; Romano, Mario; Perretti, Mauro; Montero-Melendez, Trinidad (Frontiers in Pharmacology, 2018)
Resolution Pharmacology identifies drugs developed on the biology of the resolution phase of inflammation, the complex molecular and cellular network of events that ensure the tight temporal and spatial control on the inflammatory response. As such, new anti-inflammatory and pro-resolving drugs could derive from pro-resolving mediators and receptors. To implement faithful screening programs, however, it is important to rely on predictive signaling pathway relevant for the ultimate bio-action of interest. Herein we performed an analysis with four prototypical melanocortin receptor (MC1,3,4,5) agonists. The choice fell on the natural agonist αMSH, the small molecule BMS-470539, and the synthetic derivatives [DTrp8]-γMSH and [Nle4,D-Phe7]-αMSH. We used human macrophages and quantified the effect of the four agonists on inhibition of cytokine release and promotion of efferocytosis. All agonists (1-10µM) significantly inhibited cytokine release by LPS-stimulated cells whereas [DTrp8]-γMSH was the most effective in inducing efferocytosis (~60% increase). To study sthe signaling profile, we monitored cAMP accumulation and ERK1/2 phosphorylation, and constructed biased plots that revealed a marked biased profile of [DTrp8]-γMSH towards phospho-ERK1/2. Correlation matrix analysis of all data pointed at phospho-ERK1/2 at any receptor as the most prominent pathway to attain pro-phagocytic actions, and MC1 receptor as the most relevant to drive anti-cytokine effects. In conclusion, the present study highlights the need to associate single-target signaling data with relevant functional outcomes. In this manner, we would increase our chances to optimize drug discovery programs during the early target validation and hit-to-lead phases.